Language planning and policy in Africa - Baldauf, Richard B., 1943-; Kaplan, Robert B. (Language planning and policy., 2004)
This volume covers the language situation in Botswana, Malawi, Mozambique and South Africa explaining the linguistic diversity, the historical and political contexts and the language situation in the early 21st century.